Does COVID-19 Impact Less on Post-stroke Aphasia? This Is Not the Case - Pisano, Francesca; Giachero, Alberto; Rugiero, Cristian; Calati, Melanie; Marangolo, Paola (Frontiers in Psychology, 2020)
Background: COVID-19 pandemic has broadly affected the people’s mental health resulting in severe psychological consequences. One of the leading causes of long-term disability worldwide is aphasia. The language changes experienced by a person with aphasia (PWA) often have sudden and long lasting negative impact on social interaction, quality of life and emotional well-being. The main aim of the present study was to investigate the impact of COVID-19 on the different psychosocial dimensions which affect PWA. Methods: The study included 73 PWA and 81 elderly matched controls. All patients were in the chronic phase. They all had already completed the rehabilitation program which left them with different degree of language deficits (i.e. severe vs. mild vs. moderate). All participants were administered, through an online survey, the Hospital Anxiety and Depression Scale (HADS). PWA took also part in the Stroke and Aphasia Quality of Life Scale Questionnaire (SAQOL-39). Results: Although the comparison between the pre-and-during COVID-19 period led to a deterioration of scores in all questionnaires in both groups (PWA vs. control), with a significant increase in depression and anxiety symptoms, lower rate of depression and anxiety were found in PWA compared to the healthy group. Significant deterioration was also present in PWA in the communication and psychosocial scales of the SAQOL-39 test which correlated with the observed changes in the psychological domains. Interestingly, the results were not significantly influenced by the degree of aphasia severity. Similarly, in both groups, none of the demographic variables (gender, age and educational level) significantly affected the scores in the different subscales. Conclusions: These evidence which, at first glance, seems to suggest that PWA have been partially spared from the impact of COVID-19, actually masks a dramatic situation that has always affected this population. Indeed, given that PWA already live in a state of social isolation and emotional instability, we believe that these conditions have, paradoxically, limited the effects of the coronavirus. Since COVID-19 had anyway worsened our patients’ performance, possible suggestions are discussed for people who are no longer followed in therapy in order to avoid further relapse on their communication skills.